2020
DOI: 10.1136/bmjopen-2019-036331
|View full text |Cite
|
Sign up to set email alerts
|

Organisational and individual characteristics associated with glycaemic control among patients with type 2 diabetes: cross-sectional study in China

Abstract: ObjectiveThere is a high prevalence of poor glycaemic control among patients with type 2 diabetes (T2DM) in China. This study aimed to explore both organisational and individual characteristics associated with glycaemic control among patients with T2DM.DesignCross-sectional survey.SettingShandong Province, China.ParticipantsThe participants were 2166 patients with T2DM and 337 healthcare providers from 36 urban communities and 36 rural villages in Shandong Province.Primary and secondary outcome measuresMultist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The data were checked carefully by professionals to verify accuracy and completeness [ 20 ]. Awareness was defined as the proportion of individuals who reported a history of physician-diagnosed diabetes [ 15 ]. Control was defined as the proportion of patients with diabetes with FPG < 7.0 mmol/L, which indicated that self-reported history of diagnosed diabetes patients with FPG < 7.0 mmol/L at this physical examination were considered to have glucose control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were checked carefully by professionals to verify accuracy and completeness [ 20 ]. Awareness was defined as the proportion of individuals who reported a history of physician-diagnosed diabetes [ 15 ]. Control was defined as the proportion of patients with diabetes with FPG < 7.0 mmol/L, which indicated that self-reported history of diagnosed diabetes patients with FPG < 7.0 mmol/L at this physical examination were considered to have glucose control.…”
Section: Methodsmentioning
confidence: 99%
“…Poor diabetes control rates impose a significant financial burden on individuals, families, healthcare systems, and countries. A study suggested that approximately $110 billion (12% of total health expenditure) was spent on the treatment and management of patients with diabetes in China in 2015 [ 15 ]. Thus, it is imperative to identify factors that affect blood glucose control to prevent and delay diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is a complicated and multi-factorial disease, and is a serious threat to global public health. It was reported that in China there are over 100 million patients with diabetes and the prevalence rate is still on the rise [22]. Therefore, this population-based case-control study was set up, and firstly demonstrated the effects of CYP19A1 and CYP1A2 gene polymorphisms on the T2DM susceptibility.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies also demonstrated that the enzyme activity of CYP1A2 and the speed of caffeine metabolism are increased in the T2DM group because of a higher caffeine intake [21]. The gene expression of CYP1A2 was also found to decrease in mice fed a high-fat diet [22]. In all above mentioned studies, researches have examined the functional activity of CYP1A2 in T2DM, but none of them focused on the genetic association.…”
Section: Introductionmentioning
confidence: 99%
“…Current projections estimate that between 2017 and 2045 the number of people suffering from diabetes will increase more than 50%, with the vast majority diagnosed with T2DM (Cho et al, 2018). In 2017, the prevalence of diabetes in China was 11.2% (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%